The Right to Health And Barriers to Health Services for Refugees and Internally Displaced Persons: Review of Foreign Literature - A. I. Dobrieva; P. I. Ananchenkova (Здоровье мегаполиса, 2023)
Introduction. All over the world, the number of people forced to flee their homes due to conflict, violence, and persecution is now higher than at any time in human history. Migrants, refugees, and other citizens belonging to the category of internally displaced persons have the right to health and medical care in the host country based upon the basic principles of humanitarian law and a number of international legal documents. However, the practice of providing medical care in the host country varies depending on the legislation and resources of the national healthcare system.The purpose of this study was to consider the barriers to the accessibility of medical care for migrants, refugees, and other internally displaced persons.Materials and methods. The research was mainly carried out using a content analysis of scientific literature published by foreign researchers on the accessibility of medical care to internally displaced persons, refugees, persons seeking citizenship, and other categories of migrants.Results. The study showed that it was challenging to collect complete data on the number of people deprived of the right to medical care during the registration procedure in the host country. The health status of asylum seekers depends on environmental and social factors; in addition, they face unique problems related to the healthcare system of the host country. In general, the global situation concerning access to medical care should be considered catastrophic. Despite legislative and programmatic achievements both within the framework of international humanitarian law and within countries, the provision of health services to migrants, refugees, and stateless persons remains a challenging issue. Thus, a huge number of people cannot exercise their rights to health and medical care.